Safety, Adherence, Enzymatic Activities, and Application Effects of Oral Probiotic Candidates for Shortfin Eel (Anguilla bicolor bicolor) - Dewanti, Andita Ratih; Putri, Anggi Octari; Istiqomah, Indah; Isnansetyo, Alim (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Aquaculture of the shortfin eel (Anguilla bicolor bicolor) has been plagued by low survival and growth due to the low tolerance to water quality and feed. The microbiota and shape of the fish intestinal tract influence the immune and digestive systems. The use of bacterial probiotics is fascinating to enhance the digestion system. This study aimed to characterize bacterial probiotic candidates’ safety and potential probiotic features for shortfin eel (A. bicolor bicolor) aquaculture. The safety, adherence, and enzymatic activity of three bacterial strains (Bacillus sp. PCP1, Lactococcus sp. JAL 37, and Enterobacter sp. JC05) were investigated. An oral application test was performed on shortfin eel (n=880, 15 g) every four days with 0, 3x103, 3x105, and 3x107 CFU/g diet dosages in quadruplicates for two months. At the end of the experiment, total cultivable bacteria and intestinal morphology were assessed. Based on the hemolytic test and intraperitoneal injection, the bacterial strains were considered harmless. In an in vitro investigation, the bacteria attached to shortfin eel intestinal epithelial cells. An agar diffusion method validated the proteolytic, lipolytic, and cellulolytic activities. In vivo feeding tests with the bacterial cocktail lowered the total viable bacteria in the gut while preserving the gut histology. Bacterial strains of the present study are potential probiotic candidates for shortfin (A. bicolor bicolor) aquaculture. © 2022 Faculty of Fisheries and Marine Universitas Airlangga.